De dentro da rede: delineamentos e nuanças de um conceito (From within the network: delineations and nuances of a concept) - DOI: 10.5752/P.2237-8871.2013v14n21p52 - Silva, Elias Coimbra da (Cadernos de História, 2013)
Atualmente e tendo em vista as condições objetivas da sociedade, impõe-se o estudo sobre as Redes. Nesse sentido, a Geografia apresenta uma trajetória interessante de pesquisas sobre o Espaço, mencionando, há pelo menos oito décadas, as Redes Urbanas. Entretanto, os liames que unem os conceitos-chave, como Espaço, Poder e Território, não estavam ainda estabelecidos, nem as relações entre os vários fenômenos reticulares estavam claras. Desse modo, propomos, no presente artigo, resgatar essa trajetória de pesquisas, apontando as transformações no objeto propriamente geográfico: o Espaço, até que ele atingisse a dimensão política da territorialidade. Na sequência, indicaremos de que modo as Redes são compreendidas pela Geografia e qual a relevância social delas hoje. Mas, não descuidaremos das limitações da teoria, apontando, para tanto, o grande demérito dos fenômenos reticulares tão apreciados pelos estudiosos, sobretudo aquele denominado Cidade Global. Abstract Considering the objective conditions of society, the study of Networks imposes itself today. Accordingly Geography presents an interesting history of research on the space, including on this modality in question Networks. There are at least eight decades, this science was already talk in Urban Networks and however, the bonds which unite the key concepts, such as Space, Power and Territory, were not yet established. Likewise, the relationships among the various Network phenomena were not clear. Thus, we propose in this article to rescue this trajectory of research indicating the transformations into the main object of geography: Space, until he could reached to the political dimension of territoriality. Following, we will indicate how the Networks are understood by the Geography and what their social importance today. But we will not ignore the limitations of the theory and thus, we will indicate the demerits of Network phenomena, so praised by researchers, especially the one called: Global City. Keywords: Space; Power; Territory; Netwoks; Global City.